1994
DOI: 10.1159/000204205
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Intoxication Presenting with Macrocytosis and Peripheral Neuropathy, without Anemia

Abstract: A case of arsenic intoxication associated with macrocytosis and neuropathy, without anemia, is presented. Evaluation of a 68-year-old man with a long history of peripheral neuropathy and persistent macrocytosis revealed exposure to an insecticide. Analysis of urine and hair revealed elevated levels of arsenic. A short course of d-penicillamine failed to promote urinary excretion of arsenic. Removal of the insecticide resulted in resolution of macrocytosis and slight improvement of neuropathy. This case emphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Various case reports and studies have revealed that exposure to As has resulted in various forms of cancer and peripheral neuropathy. 7,17,18 Acute and chronic exposure to As Acute A single exposure to a high dose may lead to severe reactions such as diarrhea, vomiting, pain, dehydration and weakness. Nowadays, acute intoxication rarely occurs in western European countries; if it occurs, it is usually the result of intentional (suicide or homicide) or accidental poisoning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various case reports and studies have revealed that exposure to As has resulted in various forms of cancer and peripheral neuropathy. 7,17,18 Acute and chronic exposure to As Acute A single exposure to a high dose may lead to severe reactions such as diarrhea, vomiting, pain, dehydration and weakness. Nowadays, acute intoxication rarely occurs in western European countries; if it occurs, it is usually the result of intentional (suicide or homicide) or accidental poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Various case reports and studies have revealed that exposure to As has resulted in various forms of cancer and peripheral neuropathy. 7,17,18…”
Section: Introductionmentioning
confidence: 99%
“…Chronic arsenic toxicity is characterized by macrocytosis, pancytopenia, hyperkeratotic lesions noted on the extremities, hyperpigmented melanosis described as "raindrops in the dust", bronze pigmentation, GI symptoms, anemia, and liver disease [6,27,28]. In addition, Mees' lines -transverse white striae on the fingernails (Fig.…”
mentioning
confidence: 99%
“…In addition, Mees' lines -transverse white striae on the fingernails (Fig. 1), a sensation of a metallic taste [6] and peripheral neuropathy have all been characterized in chronic arsenic exposure [27].…”
mentioning
confidence: 99%
“…Previous studies found that cutaneous papillomatosis in camels and cattle resulted in substantial alterations in the hematological parameters, including a significant decrease in total erythrocytes count, Hb concentration, and PCV [ 8 , 23 ]. The development of anemia associated with papillomatosis may be attributed to the marked off-food as disease sequelae or due to the variety of cytokines involved in the chronic inflammatory process [ 29 ]. BP causes neutropenia, lymphopenia, and consequently, the development of leucopenia due to its action to form the circulating leucocytes and/or release endogenous corticosteroids in response to stress [ 30 ].…”
Section: Discussionmentioning
confidence: 99%